Estimating the Global Prevalence of Mass Public Shootings - Duwe, Grant (International journal of offender therapy and comparative criminology, 2023)
Previous studies have yielded widely divergent conclusions about the percentage of all mass public shootings globally that take place in the US, ranging from a low of 3% to a high of 36%. Because of documented underreporting of lower-severity attacks involving fewer than 10 victim fatalities in US cases in these studies, it is reasonable to assume that this underreporting issue also applies to their measurement of mass public shootings outside the US. To estimate the total number of mass public shootings worldwide, we use multiple assumptions and modeling approaches, including a hierarchical Bayesian model. Our estimates show the US accounted for anywhere between 16% and 26% of the world’s mass public shootings during the 1976 to 2012 period. These estimates suggest the US share of the total is between four and six times higher than its 4% share of the world’s population.